(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2023)
This comprehensive article delves into the intricate relationship between science, technology, and innovation, dissecting their pivotal role in shaping contemporary economic landscapes. It underscores the influence of ICT, innovation, and government policies in driving multifactorial productivity and economic growth. The article sheds light on the evolving nature of innovation, emphasizing the need for collaboration between scientific research and industry for mutual benefit. Additionally, it discusses challenges such as mobility of scientists, intellectual property rights, and the changing dynamics of innovation in small startups. The data-driven analysis provides valuable insights for policymakers, emphasizing the significance of science and technology in fostering economic development and social progress.